Effectiveness administration of cow rumen liquid at various levels of carbohydrates in feed on nutrient digestiveness and feed efficiency of milk fish (Chanos chanos Forsskal) - Andi Masriah; Muhammad Haritza Laitte (Sekolah Tinggi Ilmu Pertanian Wuna, 2021)
Efforts to reduce protein in fish feed by maximizing the use of carbohydrates as an energy source must be supported by exogenous enzymes. One source of exogenous enzymes that can be used as a polysaccharide degrading agent easily obtained and wasted is rumen liquid in slaughterhouses (RPH). This study aims to determine the most effective carbohydrate level after being given rumen liquid as a source of exogenous enzymes in maximizing nutrient digestibility and feed efficiency in milkfish (Chanos chanos Forsskal). This study was designed using a Completely Randomized Design (CRD) which consisted of 4 treatments and three replications. Thus there were 12 experimental units. The treatments tested were feeds with various levels of carbohydrates (27.81%; 39.50%; 46.97%; and 56.75%) then given cow rumen liquid as a source of the enzyme at a dose of 80 mL/100 g of feed. Nutrient digestibility and feed efficiency data obtained were analyzed by analysis of variance (ANOVA) and continued with the W-Tuckey test. The results showed that feeding with various levels of carbohydrates in the feed that was first given cow rumen liquid waste had a significant effect (P<0.05) on fibre digestibility, carbohydrate digestibility, and feed efficiency of milkfish, but had no significant impact (P>0.05) on total digestibility, protein digestibility, and fat digestibility of milkfish. The most effective carbohydrate level in feed after being given cow rumen liquid which can optimize nutrient digestibility and feed efficiency of milkfish, is 46.97%.